2011
DOI: 10.2741/e332
|View full text |Cite
|
Sign up to set email alerts
|

SNAT2 transceptor signalling via mTOR A role in cell growth and proliferation

Abstract: Introduction 3. Materials 3.1 Materials 3.2 Cell Culture 3.3 Analysis of cell number, size and intracellular amino acids 3.4 SDS-PAGE and immunoblotting 3.5 Measurement of System A uptake 3.6 Proteomic analysis of TAP-tagged SNAT2 complexes 3.7 Statistical analysis 4. Results 4.1 MCF-7 cells express SNAT1, SNAT2 and exhibit functional System A transport 4.2 Effects of sustained System A inhibition on cell growth and proliferation 4.3 Chronic cell incubation with Me-AIB and intracellular amino acid levels 4.4 S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(6 citation statements)
references
References 46 publications
2
4
0
Order By: Relevance
“…Alternatively, SNAT2 could mediate accumulation of amino acids via tertiary active transport involving endogenously expressed transporters which then could activate mTORC1. Our results support the notion that SNAT2 represents a likely candidate as an important mTORC1 activator/accelerator as has been previously proposed (Hyde et al, 2007;Baird et al, 2009;Pinilla et al, 2011;Poncet and Taylor, 2013;Broer and Broer, 2017;Broer, 2018;Hoffmann et al, 2018). The activation of mTORC1 by SNAT2 represents an alternative mechanism to the long-suggested combined action of the amino acid transporters LAT1 and ASCT2 (Nicklin et al, 2009).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Alternatively, SNAT2 could mediate accumulation of amino acids via tertiary active transport involving endogenously expressed transporters which then could activate mTORC1. Our results support the notion that SNAT2 represents a likely candidate as an important mTORC1 activator/accelerator as has been previously proposed (Hyde et al, 2007;Baird et al, 2009;Pinilla et al, 2011;Poncet and Taylor, 2013;Broer and Broer, 2017;Broer, 2018;Hoffmann et al, 2018). The activation of mTORC1 by SNAT2 represents an alternative mechanism to the long-suggested combined action of the amino acid transporters LAT1 and ASCT2 (Nicklin et al, 2009).…”
Section: Discussionsupporting
confidence: 91%
“…The method developed here can also be used to investigate amino acid signaling, the components of which are highly conserved in multicellular eukaryotes (Panchaud et al, 2013;Saxton and Sabatini, 2017;Tatebe and Shiozaki, 2017;Javed and Fairweather, 2019). Our results support the concept of SNAT2 as a transceptor (Pinilla et al, 2011), because mTORC1 activation was observed at time points where cytosolic leucine was barely increased. Another SNAT2 substrate glutamine has also been shown to activate mTORC1 in HepG2 and HeLa cells independent of the cytosolic Leu concentration, also suggesting SNAT2 can activate mTORC1 as a transceptor using glutamine (Chiu et al, 2012).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Our study suggests that glucose sensing plays a crucial role in regulating the basal level astrocyte autophagy ( 34 , 35 , 36 ). The recycling of the glucose transporter on the plasma membrane is a dynamic and highly regulated process.…”
Section: Discussionmentioning
confidence: 76%
“…Transceptors have been identified in other organisms, such as GT1 in Leishmania mexicana 57 and GLUT2 in mice 585960. Finally, the concept of transceptors has also emerged in human cells with the identification of h CNT1 61 and h SNAT2 626364. Hence, the concept of transceptors seems to be conserved throughout evolution in eukaryotic organisms.…”
Section: Discussionmentioning
confidence: 99%